2008
DOI: 10.1243/09544100jaero274
|View full text |Cite
|
Sign up to set email alerts
|

Formation, structure, and development of near-field wing tip vortices

Abstract: The current experimental study investigates the details of the formation, structure, and development of wing tip vortices that are generated by an aerofoil of NACA0012 profile having a rectangular planform of 151 mm chord using the particle image velocimetry technique. Experiments have been carried out at different angles of attack, which affect the vortex strength, vortex size, tangential velocity, and vorticity distribution along the downstream stations at chord lengths ranging from x/ c = 0.1 to 1.6, at a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…PIV measurements on squared tip by Birch et al [8] confirmed the multiple vortices structure in the initial rolling-up of the vortex and they showed both axial velocity deficit and excess in the vortex centre at a distance of 1.5 chords from the trailing edge. Karakus et al [9] concluded that the tip region is dominated by the strong interaction between the multiple secondary vortices and the primary vortex. Zuhal and Gharib [10] found this interaction also in the wake up to 3 chords of distance from the wing; they also found a correlation between a higher fluctuation of the primary vortex location and the presence of strong secondary vortices.…”
Section: Introductionmentioning
confidence: 99%
“…PIV measurements on squared tip by Birch et al [8] confirmed the multiple vortices structure in the initial rolling-up of the vortex and they showed both axial velocity deficit and excess in the vortex centre at a distance of 1.5 chords from the trailing edge. Karakus et al [9] concluded that the tip region is dominated by the strong interaction between the multiple secondary vortices and the primary vortex. Zuhal and Gharib [10] found this interaction also in the wake up to 3 chords of distance from the wing; they also found a correlation between a higher fluctuation of the primary vortex location and the presence of strong secondary vortices.…”
Section: Introductionmentioning
confidence: 99%
“…Several possible definitions of the vortex core location exist; the method used in this work was the location of maximum (absolute) vorticity. 6,28 The advantage of this procedure was in its ease of implementation. However, only a few points are used when calculating the velocity gradients meaning that this method is sensitive to spurious velocity data.…”
Section: Particle Image Velocimetry Measurementsmentioning
confidence: 99%
“…Tip vortices shed from rotor and wind turbine blades can lead to rotor noise, mechanical fatigue, and vibration. 1,6 Lastly, various research has identified the flap side edge vortex as being an important component of high lift device noise. 7 Therefore, any new flow control technique developed that can control the tip vortex flow field could have a wide range of applications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the near-field structure has been measured using different experimental techniques. [27][28][29][30] Experimental measurements several chords downstream, which are more relevant for the present work, have been recently made, using LDA and/or particle image velocimetry ͑PIV͒ techniques, by Devenport et al 31 and by Roy. 32 These authors fitted their experimental results to a q-vortex model and to a two-core scales vortex model, respectively.…”
Section: Introductionmentioning
confidence: 99%